Autonomous bioluminescence emission from transgenic mice - Kiszka, Kamila Anna; Dullin, Christian; Steffens, Heinz; Koenen, Tanja; Rothermel, Ellen; Alves, Frauke; Gregor, Carola (Science advances, 2025)
The bacterial bioluminescence system can be applied to produce autonomous bioluminescence in mammalian cells. Until now, the system has only been stably inserted into cells cultured in vitro. Here, we report the generation of an autobioluminescent transgenic mouse line constitutively expressing the genes of the bacterial bioluminescence system, enabling substrate-free in vivo luminescence imaging of a living mammal.
Gesehen am 01.12.2025